Grasshoppers (orthoptera) - Camacho, Juan Pedro M.; Cabrero, Josefa; López-León, Maria Dolores; Cabral-de-Mello, Diogo C. [UNESP]; Ruiz-Ruano, Francisco J. (Taylor & Francis, 2014)
Grasshoppers belong to the insect order Orthoptera, which also includes locusts and crickets. This order comprises more than 26,000 species (http://orthoptera.speciesfile.org) with global distribution and higher diversity in the tropics. The name of the order is derived from “orthos,” meaning “straight,” and “pteron,” meaning “wing.” Most orthopteran species are included in two main suborders: Ensifera, including the long-horned grasshoppers (superfamily Tettigonioidea) and several types of crickets (Grylloidea and Gryllacridoidea), and Caelifera, including the short-horned grasshoppers (Acridoidea), the grouse locusts (Tetrigoidea) and the pigmy mole crickets (Tridactyloidea).